Poverty and sickness in modern Europe : narratives of the sick poor, 1780-1938 - Gestrich, Andreas; Hurren, Elizabeth T.; King, Steven (Continuum International Publishing Group, 2012)
This book provides a genuinely pan-European analysis of pauper narratives, focusing on the experiences of the sick poor in England, France, Germany, Ireland, Luxembourg, Scotland, Spain, Sweden, Switzerland and Wales. The contributions highlight the value of pauper narratives for exploring the agency, rhetoric and experiences of the poor and sick poor, significantly enhancing our understanding of the ways in which national and regional welfare systems operated. By foregrounding the particular experiences and strategies of the sick poor, this volume helps to establish and understand the central sentiments of the relief system and the core experiences of those under its care. Â What emerges is a demonstration that how a relief system treated its sick poor and how those sick poor were able to navigate the system tells us more about welfare history than analysis of any other group.